INITIAL EVALUATION OF AGRONOMIC TRAITS IN NEW APPLE VARIETIES - Tashbaev Shukhratbek Tursunovich; Khodzhaev Khamidullo Shakhobiddinovich; Urinov Dilmurodjon Mirzamakhmudovich (European Science Publishing, 2025)
This article presents data on several characteristics of late foreign apple varieties "Modi," "Liberi," "Jeromin," "Red Paulo," and "Starking Delicious" planted with a spacing of 4x2.5 meters at the Andijan Scientific Experimental Station of the Research Institute of Horticulture, Viticulture and Winemaking named after Academician M. Mirzaev, located in the Izboskan district of Andijan region. The characteristics studied include fruit color, yield, weight of individual fruits, fruit size, marketability, outer skin, fruit stem length, presence of stone cells, seed cavity, and number of seeds, as observed under the climatic conditions of the experimental station.